Influence of rotated anisotropy on slope reliability evaluation using conditional random field. (November 2019) - Huang, L.; Cheng, Y.M.; Leung, Y.F.; Li, L.
Abstract: Due to various geological processes, rotation of anisotropic soil fabric is commonly observed in nature. This paper investigates the effect of rotated anisotropy on slope reliability evaluation that considers conditional random field. In this investigation, slopes under undrained and drained conditions are studied under two kinds of sampling patterns. It is observed that the rotated anisotropy is a significant factor that influence the conditional simulation. For the conditional simulation, the uncertainty of the factor of safety (FS) and failure scale is generally the highest when the sampling points are distributed along the fabric orientation, and under such circumstance, the corresponding probability of failure Pf is observed to be the highest. Besides, a given sampling pattern leading to the uncertainty reduction relative to the unconditional simulation under the commonly investigated horizontal fabric pattern may not guarantee the uncertainty reduction under other fabric patterns for anisotropically deposited soils. Also, it is interesting to observe that due to the controlling to uncertainty by the conditional simulation, under rotated anisotropy a dip slope may be estimated to be safer than a reverse slope, and for a given fabric orientation, different sampling patterns may lead to significantly different probabilities of failure.